Frequency of Factors of Wound Infection after Caesarean Section - Abdul Waris, Hafsa; Khan, Samina Rehan; Zaheer, Fareeha; Nisar, Salma; Mohsin, Rabia; Komal, Naima (Indus Journal of Bioscience Research, 2025)
Background: Surgical-site infection following cesarean section remains a chronic source of maternal morbidity. A number of factors have been implicated, but a need exists to more clearly understand and quantify their contribution by setting. The purpose of our study was to identify rates of factors causing infection of the wound after cesarean delivery, i.e., emergency cesarean delivery, procedure time, transfusion, and prolonged hospital stay. Objective:  To assess the frequency of factors leading to wound infection after caesarean section. Study Design: Cross-sectional study. Duration and Place of Study: It was conducted from November 2024 to April 2025 in the Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital Rawalpindi. Methodology: Eligible participants were over 18 years with singleton pregnancies beyond 32 weeks. Data on demographics and potential risk factors such as emergency caesarean section, prolonged procedure, blood transfusion, and extended hospital stay were collected. Wound infection was defined by standardized clinical criteria. Results: In this study a mean age of 28.69 ± 4.42 years and a mean gestational age of 37.84 ± 1.77 weeks was observed. The study identified emergency Cesarean Section (14%), prolonged procedure duration (53%), blood transfusion (24%), and prolonged hospital stay (39%) as key factors associated with wound infection. Conclusion: Emergency cesarean section, prolonged procedure duration, and blood transfusions are key contributors to wound infection following cesarean section.